Concentration of Dihydrotestosterone and 3α-Androstanediol in Naturally Occurring and Androgen- Induced Prostatic Hyperplasia in the Dog - Moore, Ronald J. (1979)
Previous studies have suggested that dihydrotestosterone accumulation in the prostate may be involved in the pathogenesis of prostatic hyperplasia in man and dog. However, the fact that the administration of 10 mg dihydrotestosterone/d to castrated, mongrel dogs (0.5 mg/kg body wt) causes little growth in the prostate, whereas identical doses of 3α- androstanediol regularly induce prostatic hyperplasia (> 14 g weight) has raised the possibility that the dihydrotestosterone accumulation may be the result rather than the cause of the pathology. To investigate the mechanism of this phenomenon, we measured the levels of dihydrotestosterone and 3α-androstanediol in prostates from 75 dogs. In both naturally occurring and 3α-androstanediol-induced prostatic hyperplasia, the levels of dihydrotestosterone were high (>5 ng/g), whereas in immature glands and glands from dihydrotestosterone-treated animals, levels were similar (2.1 and 2.6 ng/g, respectively). 3α-Androstanediol levels were no different in animals treated with dihydrotestosterone or 3α-androstanediol. Therefore, because exogenous 3α-androstanediol is a better precursor of prostatic dihydrotestosterone than exogenous dihydrotestosterone itself, the effects of treatment with larger doses (2.5 mg/kg per d) of dihydrotestosterone and 3α-androstanediol for 12 wk were examined. In these amounts, dihydrotestosterone was as effective as 3α-androstanediol in inducing the development of prostatic hyperplasia and in elevating prostatic dihydrotestosterone concentration. Because dihydrotestosterone accumulates in spontaneous prostatic hyperplasia, because the administration of sufficient amounts of dihydrotestosterone to the castrated dog can induce the development of prostatic hyperplasia, and because 3α-androstanediol induces the development of hyperplasia via conversion to dihydrotestosterone, we conclude that accumulation of dihydrotestosterone is the cause of canine prostatic hyperplasia.